The last glance at the private life of Poles in the 19th century. A last will as a historical source - Złotkowski, Dariusz (Marginesy, 2021)
Human life can be documented and evaluated in many ways, using various historical sources. This article is a modest attempt to draw the reader’s attention to one precious historical source, namely one’s last will. In micro‑scale it can constitute abasis for reconstructing many aspect of human life, such as: family, owned property or children’s education. Next, in macro‑scale, one can trace particular social or economic processes. The article analyses last wills of 13 testators representing a certain cross‑section of society. With the help of selected examples they show people’s efforts to ensure their children’s education so that they could find their place in the economic reality of the 19th century. Moreover, the analysed wills illustrate temptations that young people had to face in the era of “steam and electricity”.